Seasonal Variation of Bacterial Diversity Along the Marine Particulate Matter Continuum - Mestre, Mireia; Höfer, Juan; Sala, M. Montserrat; Gasol, Josep M. (Frontiers in Microbiology, 2020)
Seasonal dynamics of ocean prokaryotic communities in the free-living fraction have been widely described, but less is known about the seasonality of prokaryotes inhabiting the particulate matter continuum. We describe this seasonality of bacterial communities in the particulate matter continuum by sampling monthly over two years in a temperate oligotrophic coastal ecosystem and using a serial filtration (including 6 size-fractions spanning from 0.2 to 200 µm). We observed that bacterial communities in the particulate matter continuum had annual changes following seasonal oscillations, where alpha, beta and gamma diversity increased during the warm period and decreased during the cold period. Communities in each size-fraction changed gradually over time, being the communities in larger size-fractions the ones with stronger annual changes. Annual community changes were driven mainly by day length and sea surface temperature, and each size-fraction was additionally affected by other variables (e.g. smaller size-fractions by dissolved PO4 and larger size-fractions by turbidity). While some taxonomic groups mantained their preference for a given size fraction during most of the year, others varied their distribution into different size fractions over time, as e.g. SAR11, which increased its presence in particles during the cold period. Our results indicate that the size-fractionation scheme provides novel seasonal patterns that are not possible to unveil by analyzing only free-living bacteria, and that help to better understand the temporal dynamics of prokaryotes.